RESEARCHES OF CONCRETE FRACTURE STRENGTH OF THE BEAMS BY TYPE "3 BET-90" AND "3 BET-120" - Koval, P. M.; Stoyanovich, S. V. (Science and Transport Progress, 2010)
In the article the designs of new bridge reinforced concrete beams «3 Bet-90» and «3 Bet-120» 18…33 m long are given. Their main technical characteristics are presented. The fracture strength of the beams under action of live loadings is analyzed.